Oral Gingival Cell Cigarette Smoke Exposure Induces Muscle Cell Metabolic Disruption - Andrea C. Baeder; Kiran Napa; Sarah T. Richardson; Oliver J. Taylor; Samantha G. Andersen; Shalene H. Wilcox; Duane R. Winden; Paul R. Reynolds; Benjamin T. Bikman (International Journal of Dentistry)
Cigarette smoke exposure compromises health through damaging multiple physiological systems, including disrupting metabolic function. The purpose of this study was to determine the role of oral gingiva in mediating the deleterious metabolic effects of cigarette smoke exposure on skeletal muscle metabolic function. Using an in vitro conditioned medium cell model, skeletal muscle cells were incubated with medium from gingival cells treated with normal medium or medium containing suspended cigarette smoke extract (CSE). Following incubation of muscle cells with gingival cell conditioned medium, muscle cell mitochondrial respiration and insulin signaling and action were determined as an indication of overall muscle metabolic health. Skeletal muscle cells incubated with conditioned medium of CSE-treated gingival cells had a profound reduction in mitochondrial respiration and respiratory control. Furthermore, skeletal muscle cells had a greatly reduced response in insulin-stimulated Akt phosphorylation and glycogen synthesis. Altogether, these results provide a novel perspective on the mechanism whereby cigarette smoke affects systemic metabolic function. In conclusion, we found that oral gingival cells treated with CSE create an altered milieu that is sufficient to both disrupted skeletal muscle cell mitochondrial function and insulin sensitivity.